The Use of Gadgets in Supporting the increase in Motivation and Learning Outcomes of Social Studies in Seventh Grade Students at SMP - Nurul Apriliani; Nuryana Nuryana; Yunita Yunita (STKIP Taman Siswa Bima, 2025)
Teaching and learning activities are the most important activities in the school environment. But in learning activities themselves, there needs to be innovation so that students do not feel bored during learning activities and can increase student motivation and learning outcomes. One of the learning innovations can come from learning techniques, methods or media. Currently, technology is increasingly sophisticated and advanced, for example gadgets which are now not only used as a means of communication but can also be used as a supporting medium for learning that is more interesting and innovative by utilizing sophisticated features in it. In this study, an analysis of the learning system in social studies subjects was carried out, then the application of gadget media in conducting learning, for example for tests, finding learning resources and so on. With the aim of supporting learning as well as efforts to increase motivation and learning outcomes of social studies in class VII at SMP Negeri 8 Cirebon City. The results of the study are expected to contribute and input for educators in creating an increase in motivation and student learning outcomes especially in social studies subjects.